2015
DOI: 10.1200/jco.2014.57.1745
|View full text |Cite|
|
Sign up to set email alerts
|

Phase II Study of Paclitaxel Given Once per Week Along With Trastuzumab and Pertuzumab in Patients With Human Epidermal Growth Factor Receptor 2–Positive Metastatic Breast Cancer

Abstract: Purpose The CLEOPATRA (Clinical Evaluation of Trastuzumab and Pertuzumab) study demonstrated superior progression-free survival (PFS) and overall survival when pertuzumab was added to trastuzumab and docetaxel. Paclitaxel given once per week is effective and less toxic than docetaxel. We performed a phase II study to evaluate the efficacy and safety of pertuzumab and trastuzumab with paclitaxel given once per week. Patients and Methods Patients with metastatic human epidermal growth factor receptor 2–positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 20 publications
9
62
1
1
Order By: Relevance
“…Adding pertuzumab, another HER2-directed humanized monoclonal antibody, to trastuzumab does not appear to increase these risks in recent clinical trials (35, 36). Thus, the results from repeated echocardiographic monitoring on clinical trials demonstrate that the incidence of LVEF decline in patients receiving modern trastuzumab-based regimens without concurrent anthracycline is low, especially in patients without a low baseline LVEF (20, 28, 3741). These data, along with the high rate of reversibility for trastuzumab-induced cardiotoxicity, favor continued trastuzumab use even in the face of asymptomatic LVEF declines (25, 42, 43).…”
Section: Incidence Timing and Risk Factors For Trastuzumab-related mentioning
confidence: 99%
“…Adding pertuzumab, another HER2-directed humanized monoclonal antibody, to trastuzumab does not appear to increase these risks in recent clinical trials (35, 36). Thus, the results from repeated echocardiographic monitoring on clinical trials demonstrate that the incidence of LVEF decline in patients receiving modern trastuzumab-based regimens without concurrent anthracycline is low, especially in patients without a low baseline LVEF (20, 28, 3741). These data, along with the high rate of reversibility for trastuzumab-induced cardiotoxicity, favor continued trastuzumab use even in the face of asymptomatic LVEF declines (25, 42, 43).…”
Section: Incidence Timing and Risk Factors For Trastuzumab-related mentioning
confidence: 99%
“…Recently, Dang et al demonstrated that paclitaxel given once per week with T and P is highly effective and welltolerated and could be an alternative to docetaxel-based combination therapy in first and second line setting (14).…”
Section: Figure 2 Mri Images With Se T1 After Gadolinium In Axial (Amentioning
confidence: 99%
“…Так, в исследование NCT01276041, где анти-HER2-препараты применялись совместно с паклитакселом (80 мг/м 2 еже-недельно), было рекрутировано 69 больных, для 51 (74%) из которых это была первая линия лечения и для 18 (26%) вторая. Медиана ВБП составила 24,2 мес для первой ли-нии и 16,4 мес для второй линии терапии [23]. То есть схема с паклитакселом сопоставима по эффективности с терапией доцетакселом, при которой медиана ВБП со-ставила 18,7 мес [14].…”
Section: двойная блокада рецептора Her2 пертузумабunclassified